Evaluation of genetic variability in four Nigerian locally-adapted chicken populations using major histocompatibility complex-linked LEI0258 microsatellite marker - Oladejo, O.A.; Oseni, S.O.; Kyallo, Martina M.; Domelevo Entfellner, Jean-Baka; Tor, N.E.; Tiambo, Christian K.; Pelle, Roger (2023)
Major Histocompatibility Complex (MHC) is a group of genes that generally influence immune response in vertebrates, and it has been explored among different animal species in various countries. However, there is a paucity of information on its application in Nigerian locally-adapted chickens (NLAC). This research investigated genetic polymorphism, allele variability, and genetic relationships using LEI0258 major histocompatibility complex-linked microsatellite marker among four NLAC populations: Fulani × Yoruba ecotypes, FUNNAB Alpha × Noiler breeds. Blood samples were randomly collected from 50 mature birds in each population and DNA was extracted and subsequently subjected to PCR, Sanger sequencing, and bioinformatic analysis. There were two variable numbers of tandem repeats (VNTRs), with 90% of the alleles containing only one R13 and varying numbers of the R12 motifs that ranged from 1 to 19. Additional polymorphism was revealed by the presence of five SNPs and three indels in the upstream and downstream regions of LEI0258. A total of 48 alleles were observed with sizes ranging from 188 to 530 base pairs while the allele frequencies within the populations ranged from 1.9 to 29.2%. However, only 17 out of the 48 alleles had corresponding MHC-B haplotypes. Haplotypes B2, B12, and B21 found in this study had been reported to confer resistance to infectious poultry diseases especially avian influenza in locally adapted chickens. There were high allelic variability and genetic polymorphisms observed via the atypical LEI0258 microsatellite in describing the MHC-B region.